Biodegradable Temporising Matrix for Lower Limb Reconstruction following the Resection of Giant Marjolin’s Ulcer - Samuel MacDiarmid; Daniel Butler (European Burn Journal, 2022)
NovoSorb® Biodegradable Temporising Matrix (BTM) is a synthetic matrix used as an adjunct in the reconstruction of certain complex wounds. We present a gentleman who sustained severe full-thickness lower limb burns as a child which were treated with split-thickness skin grafts. In later life, he went on to develop bilateral non-healing ulcers, resulting in a left above-knee amputation and a giant circumferential right lower limb squamous cell carcinoma (SCC) encompassing the majority of the lower leg. Surgical resection and salvage of the single remaining limb was achieved with the successful application of a BTM. BTM has proven to be successful in reconstructing a small number of SCC wounds; however, to the best of our knowledge, we are the first authors to test its application in the reconstruction of a circumferential defect associated with a giant lower limb Marjolin’s ulcer.